Triton – x 100 induced hyperlipidemia and impairment of Oxidative defense system in albino rats: protective effect of Symplocos racemosa - V. RAVI KUMAR; P.SAILAJA RAO; V. ALAGARSAMY; P. SUBHASH CHANDRA BOSE (International Journal of Pharma and Bio Sciences, 2018)
The objective of the study was to evaluate the anti-hyperlipidemic and anti-oxidant profiles of methanolic extract of Symplocus racemosa (MESR) by inducing hyperlipidemia with triton – X 100 in albino rats. In this model of induction of hyperlipidemia, there was a significant elevation of cholesterol, triglycerides and low density lipoproteins (LDL) with declined high density lipoproteins (HDL) in the serum. The animals (albino rats) were divided into 6 groups of six each (n=6) and treated for a period of 21 days with MESR (100, 200 and 400 mg/kg body weight) and standard Atorvastatin (100 mg/kg body weight) orally. The blood was withdrawn from retro-orbital plexus on 22nd day for lipid profile determination and at the end of the experimental period, the rats were sacrificed, liver was isolated and homogenized for estimation of anti-oxidant enzymes, superoxide dismutase (SOD), catalase (CAT) and lipid peroxidase (LPO). MESR (200 and 400 mg/kg body weight) showed a significant reduction (bp<0.001) in cholesterol, triglycerides and LDL and VLDL (very low density lipoprotein) with elevated levels of high density lipoproteins (HDL) in the serum. In addition to this effect, MESR treatment (200 and 400 mg/kg body weight) prevented the increased formation of malondialdehyde (MDA) in liver, restored the depleted anti-oxidant enzymes SOD and CAT significantly (bp<0.001). The experimental findings demonstrated the anti-hyperlipidemic and anti-oxidant activity of MESR, which may be directly or indirectly due to its anti-oxidant activity and also due to the presence of flavanoids and saponins.